Fifty Percent Prevalence of Extracampine Hallucinations in Parkinson’s Disease Patients - Wood, Ruth A.; Hopkins, Sarah A.; Moodley, Kuven K.; Chan, Dennis (Frontiers in Neurology, 2015)
Extracampine hallucinations (EH), the sense of a presence or fleeting movement in the absence of an associated visual percept, have been reported in Parkinson’s disease (PD) patients but their prevalence, characteristics and temporal relationship to visual hallucinations (VH) remain unclear. Given that VH are predictive of cognitive impairment in PD, improved understanding of EH may have significant prognostic implications. The objective of this study was to evaluate the prevalence and characteristics of EH in a large unselected population with PD and to assess the temporal relationship between EH, VH and memory decline. Cross-sectional data were collected using a questionnaire circulated to 414 PD patients via an online patient community. Data were obtained regarding the occurrence, timing and characteristics of VH and EH and symptoms of PD, disease duration, disease severity and medication history. 50.4% of respondents reported EH and 15.5% reported VH. EH were typically experienced alongside, rather than behind, the individual (p<0.001) without clear lateralisation (p=0.438), and were more likely to be of unfamiliar presences (p<0.001). The occurrence of EH was associated with Hoehn and Yahr score (p=0.002) but not disease duration (p=0.158). EH onset was associated with VH onset (p=0.046) and occurred after the onset of anosmia (p<0.001), cognitive decline (p=0.002) and sleep disturbance (p=0.002). The reported prevalence of EH in PD patients was threefold greater than that of VH, with similar timings of onset, suggesting that EH are under-recognised and under-reported. Further work is needed to determine whether EH are predictive of cognitive decline.